2005
DOI: 10.1542/peds.2004-2189
|View full text |Cite
|
Sign up to set email alerts
|

Folate Status of Mothers During Pregnancy and Mental and Psychomotor Development of Their Children at Five Years of Age

Abstract: Folate nutritional status of mothers in the later half of pregnancy assessed by plasma and erythrocyte folate and plasma tHcy concentrations had no impact on neurodevelopment of their children at age 5. It is unknown whether our findings in a low-socioeconomic population can be readily extrapolated to other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 26 publications
6
81
0
1
Order By: Relevance
“…In contrast to these findings, another longitudinal study assessing folic acid status late in pregnancy found no significant associations with children's neurodevelopment at 5 years of age (15) . This discrepancy may be explained by the time of measuring exposure and the follow-up of a non-population-based Table 2 Association between folic acid intake from supplements in early pregnancy and child neurodevelopment at 18 months of age (n 553), the mother-child cohort 'Rhea' study, Crete Bayely-III, Bayley Scales of Infant and Toddler Development, 3rd edition.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast to these findings, another longitudinal study assessing folic acid status late in pregnancy found no significant associations with children's neurodevelopment at 5 years of age (15) . This discrepancy may be explained by the time of measuring exposure and the follow-up of a non-population-based Table 2 Association between folic acid intake from supplements in early pregnancy and child neurodevelopment at 18 months of age (n 553), the mother-child cohort 'Rhea' study, Crete Bayely-III, Bayley Scales of Infant and Toddler Development, 3rd edition.…”
Section: Discussionmentioning
confidence: 66%
“…The association between maternal blood folate status and cognitive development has been investigated in several studies (Tamura et al, 2005;Veena et al, 2010). Tamura et al (2005) did not find any relationship between maternal blood folate status ("low" vs. "normal") during the second half of the pregnancy and cognitive development of their children at the age of 5-6 years on different cognitive tests including Differential Ability Scales, Visual and Auditory Sequential Memory, Knox Cube, the Gross Motor Scale and the Grooved Pegboard.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…However, it is unclear if this mechanism contributes to AED-induced behavioral teratogenesis. Folate deficiency during pregnancy reduces neurogenesis and increases apoptosis [34], but folate nutritional status during pregnancy has not been shown to impact neurodevelopment [35]. As discussed below, there is mounting evidence that AED-induced apoptosis is the most likely candidate for the behavioral deficits.…”
Section: Proposed Mechanismsmentioning
confidence: 99%